The Identification and Conservation of Tunicaminyluracil-Related Biosynthetic Gene Clusters in Several Rathayibacter Species Collected From Australia, Africa, Eurasia, and North America - Tancos, Matthew A.; Sechler, Aaron J.; Davis, Edward W.; Chang, Jeff H.; Schroeder, Brenda K.; Murray, Timothy D.; Rogers, Elizabeth E. (Frontiers in Microbiology, 2020)
Tunicaminyluracil antibiotics are a novel class of toxigenic glycolipids that are synthesized by several soil-associated Actinomycetes. The acquisition of a tunicaminyluracil biosynthetic gene cluster (TGC) in Rathayibacter toxicus has led to the emergence of the only described, naturally occurring tunicaminyluracil-associated mammalian disease, annual ryegrass toxicity of livestock. Endemic to Australia, R. toxicus is obligately vectored by Anguinid seed gall nematodes to the developing seedheads of forage grasses, in which the bacteria synthesize tunicaminyluracils that may subsequently be consumed by livestock and result in high rates of mortality and morbidity. The potential impact of R. toxicus on U.S. agriculture has led the U.S. Department of Agriculture – Animal and Plant Health Inspection Service to list R. toxicus as a Plant Pathogen Select Agent. R. toxicus is the only characterized phytopathogenic bacterium to produce tunicaminyluracils, but numerous R. toxicus-like livestock poisonings outside Australia suggest additional bacterial sources of tunicaminyluracils may exist. To investigate the conservation of the TGC in R. toxicus and whether the TGC is present in other Rathayibacter species, we analyzed genome sequences of members of the Rathayibacter genus. Putative TGCs were identified in genome sequences of R. toxicus, R. iranicus, R. agropyri, and an undescribed South African Rathayibacter species. In the latter three species, the putative TGCs have homologs of tunicaminyluracil-related genes essential for toxin production, but the TGCs differ in gene number and order. The TGCs appear at least partially functional because in contrast to atoxigenic species, TGC-containing Rathayibacter species were each able to tolerate exogenous applications of tunicamycin from Streptomyces chartreusis. The North American R. agropyri TGC shows extensive diversity among the sequenced isolates, with presense/absense polymorphisms in multiple genes or even the whole TGC. R. agropyri TGC structure does not appear to correlate with date or location of isolate collection. The conservation and identification of tunicaminyluracil-related gene clusters in three additional Rathayibacter species isolated from South Africa, the Middle East, and the United States, suggests a wider global distribution of potentially neurotoxigenic plant-associated bacteria. This potential for additional endemic and exotic toxigenic Rathayibacter species could have widespread and severe implications for agriculture.